The effect of cellular context on miR-155-mediated gene regulation in four major immune cell types - Hsin, Jing-Ping (Nat Immunol, 2018)
Numerous microRNAs and their target mRNAs are co-expressed across diverse cell types. However, it is unknown whether they are regulated in a cellular context-independent or -dependent manner. Here, we explored transcriptome-wide targeting and gene regulation by miR-155, whose activation-induced expression plays important roles in innate and adaptive immunity. Through mapping of miR-155 targets using differential iCLIP, mRNA quantification with RNA-Seq, and 3′UTR usage analysis using polyadenylation (polyA)-Seq in activated miR-155-sufficient and -deficient macrophages, dendritic cells, T and B lymphocytes, we identified numerous targets differentially bound by miR-155. While alternative cleavage and polyadenylation (ApA) contributed to differential miR-155 binding to some transcripts, in a majority of cases identical 3′UTR isoforms were differentially regulated across cell types, suggesting ApA-independent and cellular context-dependent miR-155-mediated gene regulation. Our study provides comprehensive maps of miR-155 regulatory networks and offers a valuable resource for dissecting context-dependent and -independent miRNA-mediated gene regulation in key immune cell types.